Dual interfacial modification engineering with p-type NiO nanocrystals for preparing efficient planar perovskite solar cells. Issue 47 (23rd November 2018) - Zhang, Weina; Song, Jing; Wang, Deng; Deng, Kaiming; Wu, Jihuai; Zhang, Lan
Abstract : High-efficiency and long-term stable planar perovskite solar cells have been achieved by dual interfacial modification engineering with p-type NiO nanocrystals. Abstract : Organic–inorganic halide perovskite solar cells with excellent photovoltaic properties still have some potential for further enhancement in device performance. Charge loss and carrier recombination at interfaces in perovskite solar cells are crucial factors that inhibit the power conversion efficiency. Here, we report a simple approach to overcome the drawbacks via modifying the interfaces between charge transport layers and perovskite layers in the perovskite solar cells with NiO nanocrystals. The optimized device achieves an excellent power conversion efficiency as high as 19.47%. The interface engineering with NiO nanocrystals results in improved interface contact properties, enhanced charge transport dynamics and suppressed charge recombination in the corresponding devices, which further contribute to increased values of open-circuit voltage and short-circuit current density. Therefore, this work provides novel guidelines toward dual interfacial modification engineering to boost the performance of perovskite solar cells.